The metric measure boundary of spaces with Ricci curvature bounded below - Brué, E; Mondino, A; Semola, D (Springer, 2023)
We solve a conjecture raised by Kapovitch, Lytchak and Petrunin in [KLP21] by showing that the metric measure boundary is vanishing on any RCD(𝐾,𝑁) space (𝑋,𝖽,ℋ𝑁) without boundary. Our result, combined with [KLP21], settles an open question about the existence of infinite geodesics on Alexandrov spaces without boundary raised by Perelman and Petrunin in 1996.